2011
DOI: 10.1143/jjap.50.076503
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Extendibility of Chemically Amplified Resists for Extreme Ultraviolet Lithography: Consideration of Nanolithography beyond 22 nm Half-Pitch

Abstract: The major resist properties, namely, resolution, line edge roughness (LER), and sensitivity have trade-off relationships. The relationships among them are determined by the pattern formation efficiency. Because of these trade-off relationships, the assessment of resist performance has been a difficult task. The extraction of parameters associated with pattern formation efficiency is important for the proper assessment of resist materials. In this study, we improved the resist model and analysis procedure for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 45 publications
(63 reference statements)
1
77
0
Order By: Relevance
“…D acid was assumed to be 1 nm , for simplicity. Note that the acid diffusion constants of current high-performance resists have been evaluated to be 2−10 nm 2 s -1 [22][23][24][25][26]. D q was assumed to be 0 nm .…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…D acid was assumed to be 1 nm , for simplicity. Note that the acid diffusion constants of current high-performance resists have been evaluated to be 2−10 nm 2 s -1 [22][23][24][25][26]. D q was assumed to be 0 nm .…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…[38] The effective reaction radii for neutralization and deprotection were set to typical values of 0.5 and 0.1 nm, respectively. [23][24][25][26] LER was evaluated using [23] dx dm…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
“…The proportionality constant f LER of state-of-the-art chemically amplified resists has been estimated to be 0.17-0.31. [23][24][25][26] Other details of the reaction mechanisms and parameters have been described in ref. 39.…”
Section: Simulation Model and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By increasing the absorption coefficient to 10 m À1 , the quantum efficiency to 4, and the effective reaction radius to 0.5 nm, it has been reported that the requirements for the 16 nm node (10 mJ cm À2 sensitivity, 1 nm LER) are achievable using an exposure tool with a numerical aperture (NA) of 0.35. 27) …”
Section: Limit Of Chemically Amplified Resistsmentioning
confidence: 99%